Analysis of Distance Learning Management during the Covid-19 Pandemic - Saptono, Saptono; Suyatmini, Suyatmini; Darsinah, Darsinah (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2022)
The Covid-19 pandemic has resulted in a change in the learning system which was originally carried out face-to-face and replaced with distance learning or online. The purpose of this research is to describe distance learning management (planning, implementing, and controlling), the constraints that arise and the solutions to overcome them. The research method uses qualitative research with a case study design and an ethnographic approach. The research was conducted at SMP Negeri 27 Surakarta. Primary data sources were obtained from school principals, vice principals for curriculum, teachers, and students. Data collection techniques using in-depth interviews, observation and documentation. The validity of the data was carried out using source triangulation techniques and double checking. Data analysis techniques in this study include data reduction, data presentation and drawing conclusions. The results of the study show that: (1) Distance learning planning at SMPN 27 Surakarta includes preparation of learning instruments, preparation of teaching materials, preparation of infrastructure, teacher training, and preparation of implementation schedules; (2) The implementation of distance learning has been running well and smoothly. Implemented using an LMS in the form of Google Classroom and Zoom, and supported by the Whatsapp (WA) application; (3) PJJ control is carried out by carrying out monitoring and evaluation activities; (4) The constraints found were divided into two, namely internal constraints (obstacles in the school) and external constraints (coming from outside the school); (5) The solution to overcoming obstacles is to maximize the teacher's role, increase the diversity of file types and sources of teaching materials, optimize features in Google Classroom, and work with parents to guide children's learning during distance learning implementation. The implication of distance learning management is the need for collaboration between school principals, teachers, students, and parents so that the implementation of distance learning can run well.